(CHN)[Zn(HPO)Cl]: substitution-activated new short-wave ultraviolet phosphate with pivotal dual-property enhancement - Fang, Zhi; Pan, Yu-Ming; Han, Pei; Yang, Bing-Ping; Duan, Mei-Hong (Journal of materials chemistry. C, Materials for optical and electronic devices, 2024)
Exploration of ultraviolet phosphates with large optical anisotropy is of great significance to the development of ultraviolet lasers. Nevertheless, due to the inherent contradiction between wide band gap and large birefringence, the exploration of ultraviolet phosphates with improved optical anisotropy is a great challenge. Herein, a new short-wave ultraviolet phosphate of (C 2 H 10 N 2 )[Zn 2 (HPO 4 ) 2 Cl 2 ] was rationally obtained through a substitution-oriented design strategy, namely the excess substitution of bridging O 2− with Cl − and OH − as well as the aliovalent substitution of K + with ethylenediamine polycations with reference to the prototype of β-K 2 [Zn 2 (PO 4 ) 2 ]. Having benefitted from this substitution, (C 2 H 10 N 2 )[Zn 2 (HPO 4 ) 2 Cl 2 ] was characterized by dual property enhancement as compared with β-K 2 [Zn 2 (PO 4 ) 2 ]. Specifically, the band gap was expanded from 3.848 eV to 5.043 eV and the birefringence was dramatically enlarged from 0.011@546 nm to 0.066@546 nm, indicating the feasibility of substitution for the design of ultraviolet phosphates with enhanced birefringence. A substitution-oriented rational approach to a short-wave ultraviolet phosphate, (C 2 H 10 N 2 )[Zn 2 (HPO 4 ) 2 Cl 2 ], results in significant dual-property enhancement.